Effect of time delay in inter-hospital transfer on outcomes of endovascular treatment of acute ischemic stroke - Pardo, Keshet; Naftali, Jonathan; Barnea, Rani; Findler, Michael; Perlow, Alain; Brauner, Ran; Auriel, Eitan; Raphaeli, Guy (Frontiers in Neurology, 2023)
Background Endovascular treatment (EVT) with mechanical thrombectomy is the standard of care for large vessel occlusion (LVO) in acute ischemic stroke (AIS). The most common approach today is to perform EVT in a comprehensive stroke center (CSC) and transfer relevant patients for EVT from a primary stroke center (PSC). Rapid and efficient treatment of LVO is a key factor in achieving a good clinical outcome. Methods We present our retrospective cohort of patients who underwent EVT between 2018 and 2021, including direct admissions and patients transferred from PSC. Primary endpoints were time intervals (door-to-puncture, onset-to-puncture, door-to-door) and favorable outcome (mRS ≤ 2) at 90 days. Secondary outcomes were successful recanalization, mortality rate, and symptomatic intracranial hemorrhage (sICH). Additional analysis was performed for transferred patients not treated with EVT; endpoints were time intervals, favorable outcomes, and reason for exclusion of EVT. Results Among a total of 405 patients, 272 were admitted directly to our EVT center and 133 were transferred; there was no significant difference between groups in the occluded vascular territory, baseline NIHSS, wake-up strokes, or thrombolysis rate. Directly admitted patients had a shorter door-to-puncture time than transferred patients (190 min vs. 293 min, p < 0.001). The median door-to-door shift time was 204 min. We found no significant difference in functional independence, successful recanalization rates, or sICH rates. The most common reason to exclude transferred patients from EVT was clinical or angiographic improvement (55.6% of patients). Conclusion Our results show that transferring patients to the EVT center does not affect clinical outcomes, despite the expected delay in EVT. Reassessment of patients upon arrival at the CSC is crucial, and patient selection should be done based on both time and tissue window.